The Method for Comprehensive Quality Evaluation of Tests. Part 1 - V. M. Kukharenko; L. P. Perkhun; N. M. Tovmachenko (Статистика України, 2018)
Informatization of the modern society has led to the wide-scale and rapid introduction of distance training technologies in virtually all the categories of Ukrainian HEEs. Studies of the aspects related to applications of digital technologies in education processes are subject to close attention in Ukraine and beyond. An important component of the training process is test control of knowledge.